Carbon sequestration loss following Zostera noltei decline in the Arcachon Bay (France). (20th September 2016) - Ribaudo, Cristina; Plus, Martin; Ganthy, Florian; Auby, Isabelle
Abstract: The worldwide decline of seagrass meadows may result in the loss of relevant ecosystem services such as the carbon sequestration within marine ecosystems. In this paper, net primary production (NPP) of Zostera noltei meadows was assessed in the Arcachon Bay (SW France) with the aim of understanding the impact of meadows decline on C sequestration capacity at a basin scale. Net growth rates obtained by means of a year-long leaf-marking experiment (2005–2006) were coupled to interannual biomass measurements (1983–2010) to obtain a direct estimate of NPP. Concurrently, an indirect estimate was obtained through a mathematical model which embedded natural factors variation (temperature, light and nutrients). Z. noltei seasonal growth and leaf morphometry followed a unimodal pattern with a peak in late summer and a minimum in winter; the interannual biomass assessment showed a steadiness at spatial and temporal scales. Net primary production simulated by the mathematical model resulted lower than that obtained by the leaf-marking and biomass method. Moreover, a temporal shift among models was evident, given to the dependence of the simulation mainly on the irradiance. Daily NPP ranged from 0.4 ± 0.2 to 8.4 ± 0.4 gDW  m −2  d −1, corresponding to an annual NPP of 1134.2 ± 100.2 gDW  m −2  y −1 and to a net C fixation of 362.9 ± 88.1 g C m −2  y −1 . By considering the loss of 33% of Z. noltei meadows in the Arcachon Bay in the period 1989–2010, it can be estimated a decline of C sequestration capacity from 24, 846 ± 6030 ton C y −1 (1989) to 16, 564 ± 4020 ton C y −1 (2007) at the basin scale.